2000
DOI: 10.1097/00003446-200004000-00006
|View full text |Cite
|
Sign up to set email alerts
|

The New York State Universal Newborn Hearing Screening Demonstration Project: Ages of Hearing Loss Identification, Hearing Aid Fitting, and Enrollment in Early Intervention

Abstract: Early ages of hearing loss identification, hearing aid fitting, and enrollment in early intervention can be achieved for infants from NICUs and WBNs and for infants at risk and not at risk for hearing loss in a large multi-center universal newborn hearing screening program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
94
2
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(107 citation statements)
references
References 15 publications
10
94
2
1
Order By: Relevance
“…The result was slightly lower when compared to a series by Dalzell et al, [14] which showed presence of hearing impairment in 61% babies who were admitted in NICU.…”
Section: Discussioncontrasting
confidence: 60%
“…The result was slightly lower when compared to a series by Dalzell et al, [14] which showed presence of hearing impairment in 61% babies who were admitted in NICU.…”
Section: Discussioncontrasting
confidence: 60%
“…25,26 Although the majority of infants in the United States are now screened, several recent studies report children with less severe degrees of loss, such as UHL and MBHL, are not being identified at the expected prevalence. 2,22,[27][28][29] As noted in Table 1 In comparison, research findings in the literature reported prevalence estimates in newborns for UHL that ranged from between 0.8/1000 to 2.7/1000. 27,29 Only 1 study had published data on the prevalence of MBHL in newborns, reporting a prevalence of 0.36 28 (Table 1).…”
Section: Newborn Hearing Screeningmentioning
confidence: 88%
“…About 1-2 per 1,000 children suffer from a neonatal bilateral permanent hearing loss that requires therapy [1] . For best therapy outcome infant hearing loss has to be treated as early as possible, before basal maturational processes of the auditory pathway are terminated [2] .…”
Section: Introductionmentioning
confidence: 99%